Deep Investigation Into the Electrodeposition Model of Mg Battery Anode - Zhou, Yingmei; Wei, Zhengnan; Xu, Jing; Chen, Changguo (Frontiers in Chemistry, 2022)
Analysis of nucleation/growth dynamics is important to understand the molecular mechanism on the electrode surface. The electrocrystallization mechanism of Mg anode in aqueous electrolyte was comprehensively investigated which can help us understand the surface discharge mechanism of Mg anode and provide a new theoretical idea for the development of high performance magnesium ion battery. The influence of applied potential signals on normal growth constant and active site numbers was studied using i-t transient curves. The dimensionless processed transient curves confirmed that the initial nucleation/growth process of Mg electrode in aqueous solution followed the diffusion-controlled three-dimensional instantaneous nucleation model.